PARTISIPASI ORANG TUA DALAM MENDUKUNG PERILAKU ASERTIF ANAK SEKOLAH TERHADAP KEKERASAN SEKSUAL - Suhariyanti, Enik; Margowati, Margowati (Universitas Muhammadiyah Magelang, 2018)
Sexual violence against children is a case that requires serious handling. The increasing number of cases in Magelang Regency illustrates that people's concern for children's lives is still not optimal. Exploration of parental participation will increase the role of parents in supporting children's assertive behavior towards sexual violence that may be experienced. Objective: to determine parental participation in children's assertive behavior towards sexual violence. Descriptive sampling was obtained by descriptive research method with 96 respondents. Instruments in the form of questionnaires using focus group discussions and interviews. Research location in Donorojo Village, Mertoyudan District. Respondents are in productive age, secondary education, and have relatively much time because they do not work or work at home. Participation seen from indicator 1) parental participation in meeting the needs of children in good categories; 2) providing guidance to children including sufficient categories; 3) fulfillment of facilities prepared by parents in anticipation of the emergence of sexual violence in a good category, and 4) giving motivation so that children have assertive behavior included in the sufficient category. Conclusion: There is parental participation in children's assertive behavior in anticipation of sexual violence in school-age children in Donorojo Village, Kec. Mertoyudan Kab. Magelang. Suggestion: Efforts are needed to improve knowledge and perceptions of parents better so that they can participate optimally in anticipating sexual violence in children